O-071 Mechanical thrombectomy in anterior versus posterior circulation acute ischemic stroke: a systematic review and meta-analysis. (23rd July 2022) - Adusumilli, G; Pederson, J; Hardy, N; Kallmes, K; Hutchison, K; Kobeissi, H; Heit, J
Abstract : Background: High-quality evidence exists for mechanical thrombectomy (MT) treatment of acute ischemic stroke (AIS) due to large vessel occlusion of the anterior circulation (AC-LVO). The evidence for MT treatment of posterior circulation large vessel occlusion (PC-LVO) is weaker, largely drawn from lower quality studies specific to PC-LVO and extrapolated from findings in AC-LVO, and ambiguous with regards to technical success. We performed a systematic review and meta-analysis to compare the technical success and functional outcomes of MT in PC-LVO versus AC-LVO patients. Methods: We identified comparative studies reporting on patients treated with MT in AC-LVO versus PC-LVO. The primary outcome of interest was thrombolysis in cerebral infarction (TICI) ≥ 2b. Secondary outcomes included rates of TICI 3, 90-day functional independence, first-pass-effect, average number of passes, and 90-day mortality. A separate random effects model was fit for each outcome measure. Subgroup analyses were performed comparing studies with recruitment periods prior to 2014 versus after 2014. Results: Twenty studies with 12, 911 patients, 11, 299 (87.5%) in the AC-LVO arm and 1, 612 (12.5%) in the PC-LVO arm, were included. AC-LVO and PC-LVO patients had comparable rates of successful recanalization [OR=1.02 [95% CI: 0.79–1.33], p =0.848). However, the AC-LVO group had greater odds of functional independence at 90 days (OR=1.26 [95% CI: 1.00; 1.59], p =0.050) and lower odds of mortality at 90 days (OR=0.58 [95% CI: 0.43; 0.79], p =0.002). In the subgroup analysis, AC-LVO patients (51.8% [95% CI: 38.4–64.8]) were found to achieve functional independence more often than PC-LVO (40.7% [95% CI: 21.8–62.8%]) patients treated after 2014, but this effect was not observed prior to 2014. Conclusions: MT achieves similar rates of recanalization with a similar safety profile in PC-LVO and AC-LVO patients. Patients with PC-LVO are less likely to achieve functional independence after MT. Future studies should identify PC-LVO patients who are likely to achieve favorable functional outcomes or those in whom MT is futile. Disclosures: G. Adusumilli: None. J. Pederson: 4; C; Nested Knowledge, Inc, Superior Medical Experts, Inc. 5; C; Nested Knowledge, Inc, Superior Medical Experts, Inc. N. Hardy: 4; C; Nested Knowledge, Inc. 5; C; Nested Knowledge, Inc. K. Kallmes: 4; C; Nested Knowledge, Inc, Superior Medical Experts, Inc. 5; C; Nested Knowledge, Inc, Conway Medical LLC. K. Hutchison: 5; C; Nested Knowledge, Inc. H. Kobeissi: None. J. Heit: 1; C; ISchemaView. 2; C; Medtronic, Microvention.